(untitled) (Acta Entomologica Serbica, 2015)
Professor Dr. Božidar Ćurčić was born on 3rd July 1946 in Belgrade. After graduating at the Faculty ofScience (Biology), University of Belgrade, in 1969, his career at the university began where he spent 44years teaching and conducting scientific research.